Pediatric Obesity: Influence on Drug Dosing and Therapeutics. (24th September 2018) - Ameer, Barbara; Weintraub, Michael A.
Abstract: Obesity is an ongoing global health concern and has only recently been recognized as a chronic disease of energy homeostasis and fuel partitioning. Obesity afflicts 17% of U.S. children and adolescents. Severe obesity (≥120% of the 95th percentile of body mass index (BMI) for age, or a BMI ≥ 35 kg/m 2 ) is the fastest‐growing subgroup and now approaches 6% of all U.S. youth. Health consequences (eg, type 2 diabetes, coronary heart disease) are related in a dose‐dependent manner to severity of obesity. Because therapeutic interventions are less effective in severe obesity, prevention is a high priority. Treatment plans involving combinations of behavioral therapy, nutrition, and exercise achieve limited success. Only one drug, orlistat, is U.S. Food and Drug Administration approved for long‐term obesity management in adolescents 12 years and older. As part of comprehensive medication management, clinicians should consider the propensity for a given drug to aggravate weight gain and to consider alternatives that minimize weight impact. Medication management must take into account developmental changes as well as the pathophysiology of obesity and comorbidities. Despite expanding insight into obesity pathophysiology, there are gaps in its translation to therapeutic application. The historical construct of obesity as simply a fat‐storage disorder is fundamentally inaccurate. The approach to adjusting doses based solely on body size and extrapolating from therapeutic knowledge of adult obesity may be based on assumptions that are not fully substantiated. Classes of drugs commonly prescribed for comorbidities associated with obesity should be prioritized for clinical research evaluations aimed at optimizing dosing regimens in pediatric obesity.